Lipoprotein (a): Structure, Pathophysiology and Clinical Implications - Maranhão,Raul Cavalcante (2014)
The chemical structure of lipoprotein (a) is similar to that of LDL, from which it differs due to the presence of apolipoprotein (a) bound to apo B100 via one disulfide bridge. Lipoprotein (a) is synthesized in the liver and its plasma concentration, which can be determined by use of monoclonal antibody-based methods, ranges from < 1 mg to > 1,000 mg/dL. Lipoprotein (a) levels over 20-30 mg/dL are associated with a two-fold risk of developing coronary artery disease. Usually, black subjects have higher lipoprotein (a) levels that, differently from Caucasians and Orientals, are not related to coronary artery disease. However, the risk of black subjects must be considered. Sex and age have little influence on lipoprotein (a) levels. Lipoprotein (a) homology with plasminogen might lead to interference with the fibrinolytic cascade, accounting for an atherogenic mechanism of that lipoprotein. Nevertheless, direct deposition of lipoprotein (a) on arterial wall is also a possible mechanism, lipoprotein (a) being more prone to oxidation than LDL. Most prospective studies have confirmed lipoprotein (a) as a predisposing factor to atherosclerosis. Statin treatment does not lower lipoprotein (a) levels, differently from niacin and ezetimibe, which tend to reduce lipoprotein (a), although confirmation of ezetimibe effects is pending. The reduction in lipoprotein (a) concentrations has not been demonstrated to reduce the risk for coronary artery disease. Whenever higher lipoprotein (a) concentrations are found, and in the absence of more effective and well-tolerated drugs, a more strict and vigorous control of the other coronary artery disease risk factors should be sought.